A educação permanente e sua relação com o estabelecimento de políticas educacionais específicas para a população idosa no Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This doctoral dissertation looks at the establishment of educational policies for older people from the perspective of permanent education and educational gerontology, considering the Open Universities of the Third Age (OU3As) as precursors of education in old age. In this regard, the research problem of the study is formulated in the following question: What are the limits and the possibilities for the establishment of specific national educational policies for older people population in Brazil? To this end, the overall aim of the study is to delineate the limits and possibilities around regulating specific public educational policies for older people in the Brazilian context, starting from the LDBEN; specific objectives of the study are to: (a) describe the historical-philosophical, demographic and legal aspects of aging; (b) discuss the guarantee of the right to education for older people from the perspective of permanent education and educational gerontology; (c) demonstrate that the OU3As are precursors of structured educational actions for older people; (d) propose the establishment of educational public policies specific for older people under the LDBEN. The theoretical-methodological framework of the study draws on critical theory, especially from the perspective of Theodor Adorno, who stands up for the emancipation and overcoming of technical rationality. Additionally, the study was grounded in Both (2000), Cachioni (1999), Dátilo and Cordeiro (2015), Debert (1999), Neri (2007), Peres (2010), Oliveira (1999, 2012) and Veras (2004) to discuss the older public and the UATIs. Reflections and analyses regarding permanent education are based on Barros (2013), Freire (1996), Furter (1976, 1984) Gadotti (2007, 2009), Paiva (2007), Requejo Osorio (2003), Lima (2007), Ribeiro (2005) and Soares (2002). Data collection, based on qualitative research, relied on bibliographic and documentary analysis, whose sources encompassed the legislation, educational policies and theoretical frameworks regarding the object of study. Overall, due to the principle of hierarchy of laws and the nomothetic pillar of Brazilian jurisdiction, there is a tendency to restrict policy making and actions aimed at ensuring the rights of older adults, still not regulated in national educational legislation, thus leading to lack of educational policies targeted at older people, the result of which implies: the need to include the older population in the wording of the LDBEN as subjects of the right to education, as already ensured for other age groups, aiming to promote lifelong learning through educational policies that meet the specificities of this public, from the perspective of educational gerontology, and not restricted to programs or projects. In this vein, this study argues that, in order to ensure the human and constitutional right to education for all, including older people, educational policies regulated specifically for the older public need to be established, from the perspective of permanent education and educational gerontology. Therefore, the present study showed that the older population, formed by subjects of rights, including the right to education, is not contemplated in Brazilian educational policies, especially in the LDBEN, so that, in order to allow educational policy making specific for this population, it is necessary to implement, on a regulatory basis at the national level, the guarantee of access and permanence of older individuals in the various areas and modalities of education, by including this population in the wording of the LDBEN, allowing, from this, the unfolding of educational policies specific for older people, such as: development and implementation of a national education plan for older people, and national educational guidelines for OU3As.
Keywords: Pessoas Idosas; Política Educacional; Educação Permanente; Gerontologia educacional; Universidades Abertas à Terceira Idade; Older people; Educational Policy; Permanent education; Educational gerontology; Open Universities of the Third Age; CNPQ::CIENCIAS HUMANAS::EDUCACAO